Surgical Techniques to Improve the Soft Tissue Triangle in Rhinoplasty: A Systematic Review - Cohn, Jason E.; Shokri, Tom; Othman, Sammy; Sokoya, Mofiyinfolu; Ducic, Yadranko (Facial Plastic Surgery, 2020)
In this systematic review we aim to (1) describe the anatomy and function of the soft tissue triangle, (2) identify the existing rhinoplasty literature that discusses the role of the soft tissue triangle, (3) provide a summary of the outcome measures for soft tissue triangle techniques in rhinoplasty, and (4) demonstrate the need for further research reviewing soft tissue triangle techniques in rhinoplasty. A systematic literature review was conducted from 2002 to 2019 utilizing MEDLINE/PubMed, Embase, Ovid, and Cochrane databases with the keywords, “rhinoplasty” and “soft tissue triangle” or “facet” to identify articles that describe the anatomical significance, clinical applicability, and rhinoplasty outcomes involving the soft tissue triangle. A total of 26 studies were identified as appropriate for inclusion. The vast majority describe the relationship of structure and function of the soft tissue triangle with particular focus on notching and retraction. The soft tissue triangle is an important area of the nose often neglected in rhinoplasty. This area is a common source of patient dissatisfaction and the need for revision rhinoplasty. Due to this fact, a formal evaluation of the role of the soft tissue triangle in nasal airway patency is needed. Specific validated outcome measures such as the NOSE (Nasal Obstruction and Septoplasty Effectiveness) score or the SCHNOS (Standardized Cosmesis and Health Nasal Outcomes Survey) should be employed in the evaluation of surgical intervention to the soft tissue triangle.
Keywords: soft tissue triangle; soft facet; rhinoplasty; infratip lobule